2022
DOI: 10.3389/fpsyg.2022.810359
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessed Digital Competences of Romanian Teachers During the COVID-19 Pandemic

Abstract: Studies on the determinants of school results have shown that they depend largely on the context of learning. Concerning the pandemic, teachers have been forced to find online teaching methods, which leads us to the central issue of this study of whether the effectiveness of online education depends on teachers’ digital skills. Therefore, in this study, we analyzed the perceived digital competences of Romanian pre-tertiary cycle teachers about their professional status, school location, gender, age, taught fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Along outdated or even malfunctioning equipment, there are internet connection quality problems worldwide, which imply connection errors as well. Also, concerning the urban-rural cleavage, it has been found that teaching professionals from urban schools perceived themselves as having better digital skills than those from rural educational institutions Hatos et al [39]. There is also a crippling lack of familiarization with the teaching platforms.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Along outdated or even malfunctioning equipment, there are internet connection quality problems worldwide, which imply connection errors as well. Also, concerning the urban-rural cleavage, it has been found that teaching professionals from urban schools perceived themselves as having better digital skills than those from rural educational institutions Hatos et al [39]. There is also a crippling lack of familiarization with the teaching platforms.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%
“…In managing the implementation of online learning, differences were observed between males and females. A study conducted on Romanian population conducted by Hatos et al [39] identifies gender differences regarding self-assessed ICT skills: office digital skills are specific to women, while multimedia and online skills are perceived to be more advanced among men.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…Therefore it is important to keep in mind that students, as adults, come to courses from various backgrounds and circumstances, with different learning needs, desires and preferences (Laurian-Fitzgerald et al, 2018), and their well-being may be in an associated relationship with several categories of variables, which have not been taken into account in this study. For example, during the pandemic, teachers had to find online teaching methods and the effectiveness of online education could depend on the digital skills of teachers (Hatos et al, 2022) and students, formed rather by self-training. However, the information provided in this study provides us first with the necessary premises to raise awareness of the need for teachers to support students in learning activities in developing educational practices by fulfilling the psychological needs of affiliation and competence, which contribute to maintaining the well-being of students in the university.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we did not account for a series of variables that might have caused significant variances in our results due to their potential connection with teachers’ digital skills, such as the schools’ location (rural versus urban schools), the teacher’s subject field, or professional status (Hatos et al, 2022 ). Finally, we measured teachers’ professional experience as a linear variable, not a categorical one, as most previous studies did (e.g., Wolters & Daugherty 2007 ).…”
Section: Discussionmentioning
confidence: 99%